Electronic properties of several two dimensional halides from ab initio calculations - Barhoumi, Mohamed; Abboud, Ali; Debbichi, Lamjed; Said, Moncef; Björkman, Torbjörn; Rocca, Dario; Lebègue, Sébastien (Beilstein Journal of Nanotechnology, 2019)
Using density functional theory, we study the electronic properties of several halide monolayers. We show that their electronic bandgaps, as obtained with the HSE hybrid functional, range between 3.0 and 7.5 eV and that their phonon spectra are dynamically stable. Additionally, we show that under an external electric field some of these systems exhibit a semiconductor-to-metal transition.
Keywords: density functional theory; electronic properties; halide monolayers

(untitled) - Novoselov, K. S.; Geim, A. K.; Morozov, S. V.; Jiang, D.; Zhang, Y.; Dubonos, S. V.; Grigorieva, I. V.; Firsov, A. A. (Science, 2004)

(untitled) - Novoselov, K. S.; Geim, A. K.; Morozov, S. V.; Jiang, D.; Katsnelson, M. I.; Grigorieva, I. V.; Dubonos, S. V.; Firsov, A. A. (Nature, 2005)

(untitled) - de Heer, W. A.; Berger, C.; Wu, X.; First, P. N.; Conrad, E. H.; Li, X.; Li, T.; Sprinkle, M.; Hass, J.; Sadowski, M. L.; Potemski, M.; Martinez, G. (Solid State Commun., 2007)

(untitled) - Wang, Q. H.; Kalantar-Zadeh, K.; Kis, A.; Coleman, J. N.; Strano, M. S. (Nat. Nanotechnol., 2012)

(untitled) - Bonaccorso, F.; Sun, Z.; Hasan, T.; Ferrari, A. C. (Nat. Photonics, 2010)

(untitled) - Grigorenko, A. N.; Polini, M.; Novoselov, K. S. (Nat. Photonics, 2012)

(untitled) - Sun, Z.; Hasan, T.; Torrisi, F.; Popa, D.; Privitera, G.; Wang, F.; Bonaccorso, F.; Basko, D. M.; Ferrari, A. C. (ACS Nano, 2010)

(untitled) - Novoselov, K. S.; Jiang, D.; Schedin, F.; Booth, T. J.; Khotkevich, V. V.; Morozov, S. V.; Geim, A. K. (Proc. Natl. Acad. Sci. U. S. A., 2005)

(untitled) - Coleman, J. N.; Lotya, M.; O'Neill, A.; Bergin, S. D.; King, P. J.; Khan, U.; Young, K.; Gaucher, A.; De, S.; Smith, R. J.; Shvets, I. V.; Arora, S. K.; et al. (Science, 2011)

(untitled) - Xia, F.; Wang, H.; Jia, Y. (Nat. Commun., 2014)

(untitled) - Koenig, S. P.; Doganov, R. A.; Schmidt, H.; Castro Neto, A. H.; Özyilmaz, B. (Appl. Phys. Lett., 2014)

(untitled) - Geim, A. K.; Grigorieva, I. V. (Nature, 2013)

(untitled) - Xu, M.; Liang, T.; Shi, M.; Chen, H. (Chem. Rev., 2013)

(untitled) - Lebègue, S.; Björkman, T.; Klintenberg, M.; Nieminen, R. M.; Eriksson, O. (Phys. Rev. X, 2013)

(untitled) - Debbichi, L.; Eriksson, O.; Lebègue, S. (J. Phys. Chem. Lett., 2015)

(untitled) - Debbichi, L.; Kim, H.; Björkman, T.; Eriksson, O.; Lebègue, S. (Phys. Rev. B, 2016)

(untitled) - Zhang, K.; Liu, C.; Huang, F.; Zheng, C.; Wang, W. (Appl. Catal., B, 2006)

(untitled) - Li, M.; Zhang, J.; Gao, H.; Li, F.; Lindquist, S.-E.; Wu, N.; Wang, R. (ACS Appl. Mater. Interfaces, 2016)

(untitled) - Li, M.; Li, J.; Guo, C.; Zhang, L. (Chem. Phys. Lett., 2018)

(untitled) - Sharma, I. D.; Tripathi, G. K.; Sharma, V. K.; Tripathi, S. N.; Kurchania, R.; Kant, C.; Sharma, A. K.; Saini, K. K. (Cogent Chem., 2015)

(untitled) - Rückamp, R.; Baier, J.; Kriener, M.; Haverkort, M. W.; Lorenz, T.; Uhrig, G. S.; Jongen, L.; Möller, A.; Meyer, G.; Grüninger, M. (Phys. Rev. Lett., 2005)

(untitled) - Seidel, A.; Marianetti, C. A.; Chou, F. C.; Ceder, G.; Lee, P. A. (Phys. Rev. B, 2003)

(untitled) - Kataev, V.; Baier, J.; Möller, A.; Jongen, L.; Meyer, G.; Freimuth, A. (Phys. Rev. B, 2003)

(untitled) - Shaz, M.; van Smaalen, S.; Palatinus, L.; Hoinkis, M.; Klemm, M.; Horn, S.; Claessen, R. (Phys. Rev. B, 2005)

(untitled) - Zhang, H.; Liu, L.; Zhou, Z. (Phys. Chem. Chem. Phys., 2012)

(untitled) - Siidra, O. I.; Zinyakhina, D. O.; Zadoya, A. I.; Krivovichev, S. V.; Turner, R. W. (Inorg. Chem., 2013)

(untitled) - Hohenberg, P.; Kohn, W. (Phys. Rev., 1964)

(untitled) - Zhao, L.; Zhang, X.; Fan, C.; Liang, Z.; Han, P. (Phys. B (Amsterdam, Neth.), 2012)

(untitled) - Bell, S.; Dines, T. J. (J. Phys. Chem. A, 2000)

(untitled) - Durig, J. R.; Guirgis, G. A.; Kim, Y. H.; Yan, W.; Qtaitat, M. A. (J. Mol. Struct., 1996)

(untitled) - Guirgis, G. A.; Shens, Z.; Qtaitat, M. A.; Durig, J. R. (J. Mol. Struct., 1997)

(untitled) - Zhang, X.; Li, B.; Wang, J.; Yuan, Y.; Zhang, Q.; Gao, Z.; Liu, L.-M.; Chen, L. (Phys. Chem. Chem. Phys., 2014)

(untitled) - Kresse, G.; Furthmüller, J. (Phys. Rev. B, 1996)

(untitled) - Kresse, G.; Joubert, D. (Phys. Rev. B, 1999)

(untitled) - Perdew, J. P.; Burke, K.; Ernzerhof, M. (Phys. Rev. Lett., 1996)

(untitled) - Blöchl, P. E. (Phys. Rev. B, 1994)

(untitled) - Monkhorst, H. J.; Pack, J. D. (Phys. Rev. B, 1976)

(untitled) - Paier, J.; Marsman, M.; Hummer, K.; Kresse, G.; Gerber, I. C.; Ángyán, J. G. (J. Chem. Phys., 2006)

(untitled) - Togo, A.; Oba, F.; Tanaka, I. (Phys. Rev. B, 2008)

(untitled) - Gonze, X.; Lee, C. (Phys. Rev. B, 1997)

2016 IEEE International Conference on Electro Information Technology (EIT) - Wu, S.; Wu, D. (First principle calculations of photocatalytic properties of bismuth oxyhalides considering van der Waals correction, 2016)

(untitled) - Bernardi, M.; Ataca, C.; Palummo, M.; Grossman, J. C. (Nanophotonics, 2017)

(untitled) - Zhang, Q.; Zhou, G.; Xing, H. G.; Seabaugh, A. C.; Xu, K.; Sio, H.; Kirillov, O. A.; Richter, C. A.; Nguyen, N. V. (Appl. Phys. Lett., 2012)

(untitled) - Zhang, Q.; Li, R.; Yan, R.; Kosel, T.; Xing, H. G.; Seabaugh, A. C.; Xu, K.; Kirillov, O. A.; Gundlach, D. J.; Richter, C. A.; Nguyen, N. V. (Appl. Phys. Lett., 2013)

(untitled) - Qi, J.; Li, X.; Qian, X.; Feng, J. (Appl. Phys. Lett., 2013)

(untitled) - Yue, Q.; Chang, S.; Kang, J.; Zhang, X.; Shao, Z.; Qin, S.; Li, J. (J. Phys.: Condens. Matter, 2012)

(untitled) - Dolui, K.; Pemmaraju, C. D.; Sanvito, S. (ACS Nano, 2012)

(untitled) - Yin, Z.; Li, H.; Li, H.; Jiang, L.; Shi, Y.; Sun, Y.; Lu, G.; Zhang, Q.; Chen, X.; Zhang, H. (ACS Nano, 2012)

(untitled) - Goniakowski, J.; Noguera, C.; Giordano, L. (Phys. Rev. Lett., 2007)

(untitled) - Hörmann, N. G.; Groß, A. (ChemPhysChem, 2014)

(untitled) - Radisavljevic, B.; Radenovic, A.; Brivio, J.; Giacometti, V.; Kis, A. (Nat. Nanotechnol., 2011)

(untitled) - Liu, H.; Neal, A. T.; Zhu, Z.; Luo, Z.; Xu, X.; Tománek, D.; Ye, P. D. (ACS Nano, 2014)

(untitled) - Eda, G.; Yamaguchi, H.; Voiry, D.; Fujita, T.; Chen, M.; Chhowalla, M. (Nano Lett., 2011)

(untitled) - Gupta, S.; Shirodkar, S. N.; Kutana, A.; Yakobson, B. I. (ACS Nano, 2018)